Screening of Antibacterial and Antioxidant Activity from the Soft Corals Sinularia sp. and Sarcophyton sp. Origin Palu Bay, Central Sulawesi, Indonesia - Tanod, Wendy Alexander; Dewanto, Didit Kustantio; Ndobe, Samliok; Riyadi, Putut Har; Putra, Masteria Yunovilsa (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2019)
This study aimed to evaluate the potential antibacterial and antioxidant activities of Sinulariasp. and Sarcophyton sp. from the Palu Bay, Central Sulawesi, Indonesia. Soft corals were identified as Sinulariasp. (SC1), Sinularia sp. (SC2), andSarcophytonsp. (SC3). Antibacterial activity was examined using agar diffusion well method. Antioxidant activity was measured by the DPPH radical scavenging method. The samples were macerated in MeOH: DCM. The crude extracts were partitioned with DCM, EtOAc, and BuOH. The crude extract of Sinulariasp. (SC2) showed a very strong antibacterial activity as it was able to inhibit the growth of Staphylococcus aureusand Escherichia coliup to 10 mg/mL. Sinularia sp. (SC1) crude extract showed strong activity againstS. aureus, whereas it showed moderate against E. coli.Sarcophyton sp. (SC3) crude extract showed moderate activity against S. aureus, whereas it showed weak against E. coli. The partition fractions of the three soft coral extracts had the potential to be a potent antioxidant agent.